Comparison of Four Types of Interrogative Sentences in Chinese and Arabic Language (A Grammatical Study): Grammar - Yibing, Ding; Seman, Haji Mohammad; Suo, Yan Mei (Al-Ḍād Journal, 2023)
An interrogative sentence is a common sentence used in daily life and communication. The main purpose of an interrogative sentence is to ask questions that the inquirer does not yet know and expects to be answered. There are many types of interrogative sentences in Chinese, mainly categorized into four types, namely general interrogative sentences, special interrogative sentences, selective interrogative sentences, and repeated interrogative sentences. While each type of interrogative sentence has its unique grammatical form and way of answering, there exist similarities among them. Question marks should be added at the end of interrogative sentences, and the tone at the end of the sentence should also go high in pitch. The topic of Arabic and Chinese interrogative sentences has been discussed and studied by many linguistic experts and researchers with many rare research results achieved. Based on previous articles on interrogative sentences, as well as the researchers’ in-depth study of Arabic and Chinese interrogative sentences, but there are very few comparative studies on Chinese and Arabic interrogative sentences. Therefore, to analyze and compare interrogative sentences in these two different languages more comprehensively, researchers will summarize, compare and analyze interrogative sentences in Chinese and Arabic. This paper first adopts a descriptive method to collect information and articles about Chinese and Arabic interrogative sentences, thus laying the quantitative foundation for the research content. The information collected in this article is mainly from grammar textbooks and books written by prominent linguists in Chinese and Arabic, journals published by linguists and researchers, and doctoral and master's theses. The paper then studies various types of interrogative sentences in Chinese and Arabic as the focus, with special attention paid to the similarities and differences presented by the two languages. Keywords: Arabic interrogative sentence, Chinese interrogative sentence, interrogative tool, comparative interrogative sentence, question type.